Caddie Woodlawn - Brink, Carol Ryrie, 1895-; Hyman, Trina Schart (New York : London : Aladdin Books ; Collier Macmillan Publishers, 1990)
The adventures of an eleven-year-old tomboy growing up on the Wisconsin frontier in the mid-nineteenth century
Keywords: Brothers and sisters -- Juvenile fiction; Frontier and pioneer life -- Wisconsin -- Juvenile fiction; Newbery Medal; Wisconsin -- Juvenile fiction